SYNTHESIS, CHARACTERIZATION, AND IN VITRO ANTIMALARIAL ACTIVITY OF DIHYDROXYLATION DERIVATIVES OF TRICLOSAN - FITRIANA, WAHYU; YANUAR, ARRY; ARSIANTI, ADE; TANIMOTO, HIROKI; KAKIUCHI, KIYOMI (International Journal of Applied Pharmaceutics, 2020)
Objective: The emergence of malaria as a global health problem over the past few decades, accompanied by the rise of chemoresistant strains of Plasmodium falciparum, has emphasized the need for the discovery of new therapeutic drugs against this disease. In this study, enantiomerically enriched (enantioenriched) analogs of triclosan were synthesized and evaluated for antimalarial activity against P. falciparum cultures. Methods: Enantioselective dihydroxylation of the olefin in amide seven was performed efficiently using chiral quinine ligand (DHQ)2PHAL to yield enantioenriched dihydroxy propionamide derivative (+)-1 in moderate yields. In a similar way, the chiral quinidine ligand (DHQD)2PHAL was used as stereoselectivity agent yielded the desired enantioenriched (−)-1. The enantioenriched products were used for further in vitro assay, and accordingly the percent enantiomeric excess (% ee) was not determined. The structures of compounds were proven by spectral data (1H NMR, 13C NMR, and mass spectra). Results: The phenol moiety at the C1 position of triclosan was chemically substituted with a methoxy group, in conjunction with an introduced stereocenter in a 2,3-dihydroxy-propionamide group at C2’ position. Unmodified triclosan inhibited the P. falciparum cultures with an IC50 value of 27.2 μM. By contrast, the triclosan analogs, compounds (+)-1 and (−)-1, inhibited the P. falciparum cultures with IC50 values of 0.034 and 0.028 μM, respectively. Conclusion: Collectively, our preliminary in vitro results suggest that these triclosan analogs have potent antimalarial activity and represent a promising new treatment strategy on further development.